Expeditious and Convenient Synthesis of Polycyclic Difluoroboron Complexes of 2‐Oxoindoline‐3‐carboxamides by Tandem Reaction. Issue 11 (19th April 2016) - Mo, Shanyan; Xu, Chuangchuang; Xu, Jiaxi
Abstract: N ‐Aryl‐2‐cyanodiazoacetamides produce polycyclic difluoroboron 2‐oxoindoline‐3‐carboxamide complexes (up to pentacyclic conjugative and fused systems) directly and expeditiously in the presence of boron trifluoride etherate. The boron trifluoride serves as both a catalyst and reactant in the tandem reaction. The tandem reaction includes the carbene aromatic CH insertion, hydrolysis of the cyano group into an amide group, and boronation of the two amide carbonyl groups. The synthetic method features the advantages of wide substrate scope and excellent chemoselectivity. Abstract :